2011
DOI: 10.4028/www.scientific.net/amr.255-260.856
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Application of Horizontal Rotation Construction Method with Flat Hinge in Cable-Stayed Bridge Construction

Abstract: Rotation construction method includes building the bridge parallel to the obstacle being spanned (a river, a highway or a railway) and then rotating the superstructure into place. The method can optimize bridge construction in terms of reducing impacts on traffic, safety, and overall project budget and duration. Therefore, the method became so popular that it has been used successfully in about one-hundred bridges in China. In this paper , taking the Suifenhe cable-stayed Bridge as project background, the desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…As the core structure of the swivel bridge, the spherical hinge structure mainly includes upper spherical hinges, lower spherical hinges, and related components [7,8]. During the rotation process of the bridge, the upper and lower contact surfaces of the spherical hinge structure freely engage and rotate relative to each other under traction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…As the core structure of the swivel bridge, the spherical hinge structure mainly includes upper spherical hinges, lower spherical hinges, and related components [7,8]. During the rotation process of the bridge, the upper and lower contact surfaces of the spherical hinge structure freely engage and rotate relative to each other under traction [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…After decades of development and improvement, it has been successfully applied to hundreds of bridges throughout the world, including North America, Austria, Europe, and Asian countries. This method is especially suitable for arch bridge 8,9 , cablestayed bridge [10][11][12][13] , continuous girder bridge 14 and so on 15-18. It was first invented as a pontoon bridge for military use during World War II Statistical studies 19 have shown that the SRM method has been widely used in various bridge types after years of development. Especially after 2000, it ushered in a qualitative leap, the continuous expansion of the rotating tonnage, and even exceeded 30,000 tons in 2018 (Tangshan Erhuan Road swivel cable-stayed bridge, 33000t).…”
Section: Introductionmentioning
confidence: 99%
“…The construction period of a swivel bridge is relatively long. The construction of the beam and pier column needs to be carried out after the installation of the spherical hinge, so the swivel bridge does not start to rotate immediately, and the waiting time generally is several months or one or two years [10][11][12]. During the period of waiting time, there is generally water seepage in the foundation pit.…”
Section: Introductionmentioning
confidence: 99%